Unavailable names in the Myotis nattereri species complex. (12th July 2019) - Ruedi, Manuel; Puechmaille, Sébastien J.; Ibáñez, Carlos; Juste, Javier
Abstract: The discovery of new species of mammals in Europe is a rare event, but owing to recent progress in genetic methods used to survey current biodiversity, such discoveries have been accumulating during the last decades. The naming of these new taxa has important bearings in conservation, as this is the first step needed for them to be recognised by the scientific community but also legally. The naming of new animal species, however, needs to follow the strict rules of the International Code of Zoological Nomenclature in order to be available and to provide a stable basis for further taxonomic research. We report here a case where new names have been improperly proposed to designate distinctive lineages in the Natterer's bat species complex. As these new names do not follow several mandatory rules imposed by the Code, they are declared unavailable and are not to be used for further taxonomy studies.